Determination of Octyl Methoxycinnamate Levels On The Face Sunscreen Gel Using Uv-Vis Spectrophotometry Method - Rochmiyanti, Hidayah; Haresmita, Perdana Priya; Syarifuddin, Alfian; Kusumorini, Nindya (Majalah Farmaseutik, 2023)
Sunlight has many benefits for the health of the body, but excessive and long-term exposure to sunlight can have an impact on skin damage, such as sunburn, photoaging (premature aging), and dull skin. Ultraviolet (UV) radiation is a major cause of skin cancer, so many sunscreen gels contain UV filters. Octyl methoxycinnamate is an example of an active UV filter agent. Octyl methoxycinnamate is a cinnamic compound that absorbs light wavelengths 280 nm–320 nm (UVB). This study aims to determine the octyl levels of methoxycinnamate in sunscreen gel preparations circulating in Magelang Regency and assess whether these preparations meet the predetermined safety limits. The analysis used in this research is qualitative and quantitative analysis. Qualitative study using thin layer chromatography (TLC) with silica gel F254 as stationary phase and mobile phase n-hexane : ethyl acetate (7.5 : 2.5) and then detected on UV light at 254 nm. Quantitative analysis using UV-Vis spectrophotometer at a maximum wavelength of 310.5 nm. The results of the qualitative analysis showed that the three samples X, Y and Z were positive contain octyl methoxycinnamate. The results of the TLC showed that samples X, Y, and Z produced purple stains and had the same Rf values between the samples and the standards. Octyl methoxycinnamate levels in sample X of 0.155%; Y 0.824%; and Z 1.954%. The results obtained by the relative standard deviation (RSD) of the sunscreen gel sample were X 0.015%; Y 0.048%; and Z 0.921%. It can be concluded that the three tested sunscreen gel samples are safe for use by the general public.